2010
DOI: 10.3233/jad-2010-1338
|View full text |Cite
|
Sign up to set email alerts
|

Trace Copper(II) or Zinc(II) Ions Drastically Modify the Aggregation Behavior of Amyloid-β1–42: An AFM Study

Abstract: Formation of amyloid-beta (Abeta){1-42} amyloid fibrils, a characteristic feature of Alzheimer's disease (AD), was monitored in situ through atomic force microscopy (AFM). Well-structured amyloid fibrils slowly formed in solution within 24 hours for which high quality AFM pictures could be obtained. Remarkably, addition of either copper(II) or zinc(II) ions to the incubation medium, even at extremely low molar ratios, dramatically changed the Abeta {1-42} aggregation profile and prevented fibril formation. Agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 16 publications
5
72
0
Order By: Relevance
“…In fact the micrograph recorded at time zero shows the presence of small oligomers (≈15 nm of diameter); after 24 h of incubation a large amount of amorphous aggregates was detected. Aβ-Zn, as confirmed by CR spectroscopic assay, forms at the beginning small and unstructured aggregates that after 24 h did not increase in dimension nor assumed a well defined fibrillary structure, as already reported by our laboratory [19] and confirmed by other studies [35]. Furthermore, Aβ-Zn micrographs confirmed after 24 h the anti-aggregative role of cholesterol to the amyloid-zinc complex.…”
Section: Temsupporting
confidence: 82%
“…In fact the micrograph recorded at time zero shows the presence of small oligomers (≈15 nm of diameter); after 24 h of incubation a large amount of amorphous aggregates was detected. Aβ-Zn, as confirmed by CR spectroscopic assay, forms at the beginning small and unstructured aggregates that after 24 h did not increase in dimension nor assumed a well defined fibrillary structure, as already reported by our laboratory [19] and confirmed by other studies [35]. Furthermore, Aβ-Zn micrographs confirmed after 24 h the anti-aggregative role of cholesterol to the amyloid-zinc complex.…”
Section: Temsupporting
confidence: 82%
“…Based on TEM images, under these conditions, the morphology of the fibers generated appears quite similar for fibers formed with and without the presence of Cu 2ϩ ions. We note that previous studies by other groups using TEM did not reveal fibers in the presence of Cu 2ϩ because the high A␤ and Cu 2ϩ concentrations used caused amorphous precipitation (42)(43)(44)(45)(46). Furthermore, the Cu 2ϩ -generated fibers are capable of seeding fiber formation of fresh, metal-free A␤ as indicated by a reduction in the lag time (see supplemental Fig.…”
Section: Coppermentioning
confidence: 84%
“…These initial studies did not make the distinction between amorphous aggregates, which are nontoxic to cells, and the formation of amyloid fibers. Further investigations using the fiber specific fluorophore thioflavin T (ThT) suggested that Zn 2ϩ and Cu 2ϩ only promote amorphous aggregation of A␤ and actually inhibit fiber formation and cell toxicity (42)(43)(44)(45)(46). We became interested in the factors that promote self-association of A␤, the relationship between amorphous aggregation and amyloid fiber formation, and a role for Cu 2ϩ ions in promoting fiber formation.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Copper ions increase the aggregation rate of Aβ, [ 54 , 55 ] promoting the formation of both amyloid and amorphous aggregates . [56,57] Since absorbance changes are proportional to the formation of Aβ aggregates, including fibrillar and amorphous ones, whereas ThT is sensitive to amyloid-type aggregates only, the copper-induced aggregation process was monitored by light scattering measurements, [58,59] The turbidity of solutions containing only Aβ 1-40 (Ctrl) is very small (0.018 units) ( Figure 9). As ions.…”
Section: Superoxide Dismutase Indirect Assaymentioning
confidence: 99%